Draft Environmental Impact Report Oxnard Airport Master Plan excerpt - Michael Brandman Associates, Inc.:::::: (1985)
An excerpt from the Draft Environmental Impact Report of Oxnard Airport Master Plan which describes the existing land use around the area of the Oxnard Airport.